Recent Advancements in Animal Models of Fibromyalgia. Issue 3 (2nd October 2015) - Nagakura, Yukinori
Abstract: Objectives: The need for the development of better therapies for fibromyalgia is urgent due to the distress experienced by patients with this disorder and the escalating health care costs. A variety of animal models of fibromyalgia, including the reserpine-induced myalgia model, repeated acidic saline injection model and subchronic swim stress model, have been developed to study this disorder. This review highlights the advancements in the understanding of the characteristic comorbidities of fibromyalgia and the pathophysiology of hyperalgesia at the peripheral, spinal and supraspinal levels from studies of these models. Findings: Recent studies have described comorbidities, such as fatigue and anxiety, which are characteristic of patients with fibromyalgia. The pathophysiologies underlying these comorbidities are beginning to be explored. In addition, the pathophysiology underlying the hyperalgesia observed in animal models of fibromyalgia might include increases in acid-sensing ion channels and macrophage-mediated signals at peripheral level, increased microglia-mediated immune responses at spinal level, and neuroplastic and neurochemical changes at supraspinal brain level. Conclusions: Animal models of fibromyalgia have resulted in valuable advancements in the understanding of the main comorbidities of fibromyalgia, such as fatigue and emotional disturbances. Investigations of the mechanisms underlying the comorbidities and the hyperalgesia of fibromyalgia are important for a comprehensive understanding of the pathophysiology of fibromyalgia. Although several significant advances in the understanding of fibromyalgia have recently been made, additional studies on the pathophysiology of hyperalgesia and the main comorbidities of fibromyalgia are warranted to better understand this complex disorder and develop better therapies.